Pour un emboîtement médiatique et méthodologique - Alessandro Rossi (Images Re-Vues)
Two of Lorenzo Lotto’s paintings, Christ Taking Leave of His Mother, with Elisabetta Rota (1521) and the Portrait of Fra Gregorio Belo (1547), are interpreted as theoretical objects according to the definition of this concept by Hubert Damisch. The compositional structure and iconography of these paintings illustrates independently William J. Thomas Mitchell’s theory. According to this theory, the visual medium and the verbal medium cannot be separated, despite having clearly different characteristics. The method used here brings together Iconology and Visual Semiotics. This allows us to recognize the nesting media theory expressed in Lotto’s two paintings, beyond the specific historical subjects they represent.